A Paradox in the Theory of Optimal Stabilization - Preston, A. J. (Review of Economic Studies, 1972)
Journal Article A Paradox in the Theory of Optimal Stabilization Get access A. J. Preston A. J. Preston Queen Mary College, University of London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 4, September 1972, Pages 423–432, https://doi.org/10.2307/2296510 Published: 01 September 1972